Strategi Dan Media Pengembangan Moral Dan Agama Pada Anak Usia Dini - Nuri Arifiah Romadhoni; Muhammad Turhan Yani; Achmad Sya’dullah (Journal of Student Research, 2024)
In the Islamic religion, religious values are taught, and this includes moral values. The instillation of religious morals in children is best given from an early age. And the first person to provide this teaching is from the family environment first. The first school for children are a family, in which there is a mother who will be the first madrasah for her sons and daughters. In relation to this, the development of moral and religious values in children is obtained from their home or family. From the time the children wake up until they go back to sleep, everything is done. conceptualized by existing family rules. Therefore, family education is really needed in this case in order to develop children's moral and religious values. Talking about strategies and media for moral development in early childhood, nowadays we should be able to take advantage of the media around us and also following the development of mass media through digitalization learning. Apart from the family education that Ananda received, we can also teach you how to utilize digitalization media tools with assistance and useful use. There are also many strategies that can be used to develop the character of religious values. and morals through the media that we encounter every day and can also take advantage of the mass media that are currently developing.